Translation and mysticism: the rose and the wherefore - Wilson, Philip (Routledge studies in literary translation, 2024)
"This book examines the ways in which mysticism can tell us about translation and translation can tell us about mysticism, addressing the ancient but ongoing connections between the art of rendering one text in another language and the art of the ineffable. The volume represents the first sustained act of attention to the interdisciplinary crossover of these two fields, taking a Wittgensteinian approach to language, and investigates how mystics and their translators manage to write about what cannot be written about. Three questions are addressed overall: how mysticism can be used to conceptualise translation; the issues that mysticism raises for translation theory and practice; how mystical texts have been and might be translated. Walter Benjamin's 'the Translator's Task' is considered in detail as a controversial example of dialogue. Translation examples are given in a range of languages, and six major case studies are included, including a close reading of Exodus and an analysis of a recent radical translation of Lucretius. This book will be of interest to students and researchers in translation studies, mysticism studies, theology and literary translation, as well as practising translators"